Clinoforms as paleogeographic tools: Development of the Danube catchment above the deep Paratethyan basins in Central and Southeast Europe. (31st August 2019) - Magyar, Imre; Krezsek, Csaba; Tari, Gabor
Abstract: The Miocene marine basins of Central and Southeast Europe, once comprising the Paratethys Sea, were gradually filled with sediments during the Neogene and turned to be the catchment area of the proto‐Danube and finally that of the modern Danube. Seismic data from various parts of the large Danube catchment area show that these several hundred meter deep basins were filled by lateral accretion of river‐transported sediments, appearing as shelf edge scale clinoform sets in seismic profiles. The direction of shelf edge progradation is NW to SE (N to S, W to E) in each basin, except for the Dacian basin where NE to SW direction prevails. The age of the clinoform sets is generally younging downstream: 19–18 Ma in the North Alpine Foreland basin, 14–13 Ma in the Vienna basin, 10–9 Ma in the Danube (Kisalföld) basin, 8.6–4 Ma in the Central Pannonian basin (Alföld), ?9–5 Ma in the Dacian basin, and 6–0 Ma in the Euxinian (Black Sea) basin. In spite of this geographical and temporal pattern, only the Danube (Kisalföld) and the western and central part of the Central Pannonian basin were filled by the proto‐Danube shelf accretion. Formation of the Danube, as a longitudinal river of the Alpine foreland that gradually elongated to the east and followed the retreating shoreline of the Paratethys, most probably took place at the beginning of the Late Miocene, ca. 11 Ma ago, thus the Early and Middle Miocene shelf advance in the North Alpine Foreland and Vienna basins, respectively, cannot be attributed to a „paleo‐Danube". The clinoform systems of the Dacian basin are coeval with those of the upstream Central Pannonian basin, indicating that by the time the Danube sedimentary system reached the Dacian basin, it was already a shallow basin. The vast clinoforms of the northwestern Euxinian shelf also significantly overlap in age with the Pannonian basin ones; only the <4 Ma part of the shelf accretion can be attributed to the Danube sensu stricto . Abstract : The Neogene Paratethyan basins, strung together by the Danube from the North Alpine Foreland basin (NAFB) downstream to the Euxinian (Black Sea) basin (EB) shelf, were transformed from several‐hundred‐meter‐deep marine or lacustrine basins to shallow marine and to fluvial environments during the Neogene. As the shelf‐edge clinoform sets of these basins along the present‐day course of the Danube indicate, this process took place generally from NW to SE within each basin, and with a general temporal younging between the basins from NW to SE. In spite of this geographical and temporal pattern, however, only the Danube (Kisalföld) basin (DKB), the Central Pannonian basin (CPB), and the younger part (<4 Myr) of the EB shelf were filled by the shelf advance of the proto‐Danube; the NAFB and the Vienna basin (VB) were filled by sediment transport systems that had no temporal continuity with the modern Danube, whereas the Dacian basin (DB) had been filled by local sediment systems by the time the proto‐Danube found its way to the DB ca. 4 Mys ago.